(untitled) (Development Service Industry Management, 2025)
The article examines the priorities and means of structural reform in the regional small business sector, highlighting key areas for improving efficiency, competitiveness, and sustainability. It also analyzes the tools and mechanisms through which regional authorities and stakeholders can support the development and modernization of small enterprises. The purpose of the article is to substantiate the priorities and means of structural reform in the small business sector of Ukrainian regions. It has been found that the small business sector has undergone significant transformations: the number of active enterprises has decreased, their specialization has changed, logistical chains have been restructured, and there has been a transition to remote and online forms of activity. In the context of increased financial, market, and institutional risks, a proactive regional policy aimed at stimulating the development of small businesses, enhancing their resilience, and ensuring structural changes in the sector is particularly relevant. Key priorities for reform have been identified, including the stimulation of innovative activity, the development of human capital, the formation of a favorable regulatory environment, and the improvement of management process efficiency. As means of implementing these priorities, the article proposes grants and subsidies, preferential lending, the development of business incubators and accelerators, the digitalization of management processes, and the support of partnership networks between enterprises and authorities. The abstract emphasizes the necessity of a comprehensive approach to the modernization of small businesses under conditions of war and ongoing transformations in the external environment.